Modenas enterprise web-based systems (MEWS) framework for ecommerce solutions in Modenas / Zailani Abdullah ... [et al.] - Abdullah, Zailani; M.Saman, Md Yazid; M.Deris, Mustafa; Hassan, Pouzi (2002)
This paper is part of the Enterprise Web-based System (MEWS) proposal for Motosikal Dan Enjin Nasional Sdn Bhd (MODENAS). The main focus of this paper is on the conceptual model of e-commerce environment and an introduction to the terminology associated with the technology. The e-commerce model has been chosen due to current market trends and it is believed to be the right strategy for participation in worldwide markets globalization. Thus, a proper infrastructure and readiness of web-based applications is essential to ensure that the company is on the right track before the AFTA 2005 implementation. There are two web-based applications considered as e-commerce systems, namely Electronic Excise System (EES or e-excise) and Electronic Procurement System (EPS or e-procurement). Generally, EES will focus on the finished product (motorcycle) handling whereas EPS will concentrate on raw material purchasing (motorcycle spare part). All the topics covered here will give an overall idea of the MEWS project framework and how it rationalizes MODENAS' heterogeneous environment. Successful modeling of the complete e-commerce environment will become the benchmark and starting point for development of our own e-procurement system in the near future.